Research on "Face Swiping" Medical Service Diffusion from the Perspective of Game Theory. Issue 1 (March 2020) - Zhu, Keyu; Cheng, Peiling; Sun, Qirui; Zhang, Shanshan; Wang, Xiaojia
Abstract: "Face swiping" medical service (FSMS) is one of the important breakthroughs in the field of medical care. FSMS is at a growing stage, and whether it can develop stably in the traditional medical mode has not been well studied at present. This paper establishes an evolutionary game model to analyze the behaviors of the two main participants of FSMS (the hospitals and the patients); And it finds out the factors that affect the choice behavior of the two main participants to analyze different strategies that participants choose how influence the development of FSMS in the future. Furthermore, the profit matrix is analyzed by establishing a replicator dynamic system, and the effectiveness of the model is verified by simulation using Python3.7 software.